Trypanosomes of non-human primates from the National Centre of Primates, Ananindeua, State of Pará, Brazil - Ziccardi Mariangela; Lourenço-de-Oliveira Ricardo; Lainson Ralph; Brígido Maria do Carmo de Oliveira; Muniz José Augusto Pereira Carneiro (Memorias do Instituto Oswaldo Cruz, 2000)
Trypanosome infections were sought in 46 non-human primates captured principally in Amazonian Brazil. Twenty-two (47.8%) were infected with four Trypanosoma species: T. cruzi, T. minasense, T. devei and T. rangeli. These preliminary results confirmed the high prevalence and diversity of natural infections with trypanosomes in primates from Brazilian Amazon and were the first formal record of simian infections with trypanosomes in the State of Acre. The presence of T. cruzi-like and T. rangeli-like parasites are recorded in four new hosts.